2009
DOI: 10.1088/0022-3727/42/22/225001
|View full text |Cite
|
Sign up to set email alerts
|

Exchange bias in epitaxial Fe/Ir0.2Mn0.8bilayers grown on MgO (0 0 1)

Abstract: Exchange bias has been studied in epitaxial Fe/Ir0.2Mn0.8 (IrMn) bilayers grown by molecular beam epitaxy on MgO (0 0 1) substrates. The IrMn layer has a chemically disordered fcc structure with an epitaxial relationship of MgO(0 0 1)[1 1 0]//Fe(0 0 1)[1 0 0]//IrMn(0 0 1) [1 1 0]. In this system, exchange bias is induced during growth at room temperature without post-annealing, by applying a small magnetic field, HA, along the bcc Fe [1 0 0] easy axis. The temperature dependence of the exchange bias field and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
2
17
1
Order By: Relevance
“…Theoretically, both the coherent rotation and the DW nucleation can result in irreversible Barkhausen jumps, the two reversal mechanisms as well as the asymmetrical one have been observed in various EB systems 17,18,26,27 . We have tried to use the coherent rotation to explain the hysteresis loops for a-axis oriented MnPd/Fe EB bilayers, but the prediction for the coercivity is obviously too large 28 .…”
Section: Magnetization Reversal Mechanismmentioning
confidence: 98%
See 1 more Smart Citation
“…Theoretically, both the coherent rotation and the DW nucleation can result in irreversible Barkhausen jumps, the two reversal mechanisms as well as the asymmetrical one have been observed in various EB systems 17,18,26,27 . We have tried to use the coherent rotation to explain the hysteresis loops for a-axis oriented MnPd/Fe EB bilayers, but the prediction for the coercivity is obviously too large 28 .…”
Section: Magnetization Reversal Mechanismmentioning
confidence: 98%
“…We have tried to use the coherent rotation to explain the hysteresis loops for a-axis oriented MnPd/Fe EB bilayers, but the prediction for the coercivity is obviously too large 28 . On the other hand, by using Lorentz transmission electron microscopy, Wang et al directly observed that the magnetization reversal in epitaxial IrMn/Fe bilayers occurs through DW nucleation and propagation 26 . Inspired by these works, we tentatively extend the DW nucleation model developed for Fe/MgO(001) films to account for the magnetization reversal in epitaxial MnPd/Fe EB bilayers.…”
Section: Magnetization Reversal Mechanismmentioning
confidence: 99%
“…12,22,23 Various in situ techniques including surface x-ray diffraction 24 and x-ray magnetic circular dichroism 25,26 have been used to characterize the Fe/MgO interface structure, arriving at conflicting conclusions. Serin et al 18 measured an asymmetry in the roughness of the two interfaces, using STEM to collect electron energy-loss spectroscopy ͑EELS͒ data.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed descriptions of the growth process, the structural characterization, and junction fabrication can be found elsewhere. [22][23][24] The magnetotransport properties were measured in a physical properties measurement system using a standard fourprobe technique. Dynamic conductance ͑dI / dV − V͒ and IET spectrum ͑d 2 I / dV 2 − V͒ were measured at 30.79 Hz with an ac modulation voltage of 4 mV using a standard lock-in method.…”
mentioning
confidence: 99%